Targeted Repolarization of Tumor‐Associated Macrophages via Imidazoquinoline‐Linked Nanobodies. Issue 10 (8th March 2021) - Bolli, Evangelia; Scherger, Maximilian; Arnouk, Sana M.; Pombo Antunes, Ana Rita; Straßburger, David; Urschbach, Moritz; Stickdorn, Judith; De Vlaminck, Karen; Movahedi, Kiavash; Räder, Hans Joachim; Hernot, Sophie; Besenius, Pol; et al.
Abstract: Tumor‐associated macrophages (TAMs) promote the immune suppressive microenvironment inside tumors and are, therefore, considered as a promising target for the next generation of cancer immunotherapies. To repolarize their phenotype into a tumoricidal state, the Toll‐like receptor 7/8 agonist imidazoquinoline IMDQ is site‐specifically and quantitatively coupled to single chain antibody fragments, so‐called nanobodies, targeting the macrophage mannose receptor (MMR) on TAMs. Intravenous injection of these conjugates result in a tumor‐ and cell‐specific delivery of IMDQ into MMR high TAMs, causing a significant decline in tumor growth. This is accompanied by a repolarization of TAMs towards a pro‐inflammatory phenotype and an increase in anti‐tumor T cell responses. Therefore, the therapeutic benefit of such nanobody‐drug conjugates may pave the road towards effective macrophage re‐educating cancer immunotherapies. Abstract : Imidazoquinolines as toll‐like receptor 7/8 agonists can cell‐specifically be delivered via a macrophage mannose receptor targeting nanobodies to pro‐tumoral macrophages in the tumor microenvironment. A repolarization of their phenotype into a pro‐inflammatory state is observed affording significant decline in tumor growth. Such imidazoquinoline‐linked nanobody‐drug conjugates can be considered as promising macrophage re‐educating cancer immunotherapies.